Analisis Kelayakan Sistem Kompensasi Langsung pada Tenaga Pendidik di Sekolah TK Swasta ABD: Studi Kasus di Jakarta - Methanoia, Louise Yuve; Wolor, Christian Wiradendi; Utari, Eka Dewi (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
This study aims to analyze the feasibility of the direct compensation system applied to teaching staff at the ABD Private Kindergarten in Jakarta. The main focus is to assess whether the compensation system meets the principles of fairness, transparency, and alignment with teachers' workloads and responsibilities. A qualitative case study approach was employed, involving data collection through in-depth interviews with four educators, direct observations, and analysis of internal school documents. The findings reveal that the current compensation system fails to reflect teachers’ actual contributions and workload proportionately. The lack of objective performance evaluations and the absence of a structured salary increment mechanism were identified as key factors affecting work motivation. These results highlight the urgent need to reform compensation policies within early childhood education institutions. The study recommends the implementation of a more structured and transparent salary framework that considers years of service, educational background, and involvement in school activities. This research provides practical insights for private education stakeholders aiming to develop a more effective and sustainable compensation system that enhances both teacher welfare and educational quality.